2018
DOI: 10.5194/acp-18-7001-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic growth study in the framework of EARLINET during the SLOPE I campaign: synergy of remote sensing and in situ instrumentation

Abstract: Abstract. This study focuses on the analysis of aerosol hygroscopic growth during the Sierra Nevada Lidar AerOsol Profiling Experiment (SLOPE I) campaign by using the synergy of active and passive remote sensors at the ACTRIS Granada station and in situ instrumentation at a mountain station (Sierra Nevada, SNS). To this end, a methodology based on simultaneous measurements of aerosol profiles from an EARLINET multi-wavelength Raman lidar (RL) and relative humidity (RH) profiles obtained from a multi-instrument… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 83 publications
8
44
0
Order By: Relevance
“…As shown in Figure 4 and Table 2, both are generally constant within each layer of each case, indicating uniformly atmospheric mixing and vertical homogeneity in both cases. Therefore, the hygroscopic growth that occurred in both cases, resulting in changes in aerosol optical properties, was most likely caused by the uptake of water [54,55]. When the aerosol layer is uniformly mixed, the variation of aerosol optical properties with height can be considered mainly caused by water uptake in the aerosol layer.…”
Section: Lidar-estimated Hygroscopicitymentioning
confidence: 99%
“…As shown in Figure 4 and Table 2, both are generally constant within each layer of each case, indicating uniformly atmospheric mixing and vertical homogeneity in both cases. Therefore, the hygroscopic growth that occurred in both cases, resulting in changes in aerosol optical properties, was most likely caused by the uptake of water [54,55]. When the aerosol layer is uniformly mixed, the variation of aerosol optical properties with height can be considered mainly caused by water uptake in the aerosol layer.…”
Section: Lidar-estimated Hygroscopicitymentioning
confidence: 99%
“…The aerosol hygroscopic 17 optical enhancement factor [ ] has also also been employed, defined as the ratio between value under dry conditions (Kotchenruther et al, 1999). It can be measured by a humidified 21 tandem nephelometer (e.g., Covert et al, 1972;Feingold and Morley, 2003;Titos et al, 2018).…”
mentioning
confidence: 99%
“…TDMA and nephelometer (Bedoya-Velásquez et al, 2018). Raman lidar systems also provide 14 measurements at higher spatial and temporal resolutions which are useful for examining the 15 effects of aerosol hygroscopic growth on pollution events (e.g., Y.-F. Wang et al, 201216 Su et al, 2017).…”
mentioning
confidence: 99%
“…(b) Optical microscopic images of a particle which contained (NH 4 ) 2 SO 4 and 1,2,6-trihydroxyhexane with a mass ratio of 1 : 2.1, during an experiment in which temperature was kept at around 291 K, while RH was decreased. Reprint with permission by Bertram et al (2011). of supporting substrates (including TEM grid, Parafilm-M, aluminum foil, Ag foil, silicon wafer and cover glass) on hygroscopicity measurements using optical microscopy and concluded that TEM grids were the most suitable substrate for this application. Optical microscopy was also used to study hygroscopic properties of MgCl 2 and NaCl−MgCl 2 mixed particles (Gupta et al, 2015), and hygroscopic properties (including DRH and growth factors) of these particles were found to differ significantly from NaCl.…”
Section: Optical Microscopymentioning
confidence: 99%